Internalization of Responsibility to Protect (R2P): Responsibility to Invoke ‘Peace from Within’ Afghanistan by the Taliban Regime (2021) - Fujin Naz Haidery (NUST Journal of International Peace & Stability, 2024)
Sovereignty, concerning state authority, endows the Responsibility to Protect (R2P) the rights of citizens. This redefined and broadened scope of sovereignty is ascribed to the international norm of the R2P. The pioneering assertions of R2P were conceptualized by the UN Secretary-General Kofi Annan in ‘Two Concepts of Sovereignty’ after NATO intervened in Kosovo (1999). During a humanitarian crisis, the more serious concern lies in the unchecked systematic violations of human rights rather than the question of the legitimacy and legality of intervention by the international community. In the 2005 World Summit, Sovereignty was redefined as an R2P by the state against atrocious violations of human rights. In case of failure of the host state, the international community could intervene through the Security Council. This paper will implicitly consider the normative contours of the R2P framework while assessing the current multifaceted humanitarian crisis in Afghanistan. The post-war humanitarian crisis in Afghanistan is characterized by poverty and internal displacement. Additionally, human security concerns arise from the inter-group rivalry between the Islamic State Khorasan (ISK) and the Taliban, accompanied by human rights violations against women and ethnic minorities under the Taliban regime. Aligning with the first pillar, the responsibility to protect Afghan citizens rests with the Taliban as the sovereign authority of the state. However, internalizing the principles of the Responsibility to Protect (R2P) can pave the way for prospective peace in Afghanistan.